Breaking a Spell : Odd Craft, Part 6. - Jacobs, W. W. (William Wymark), 1863-1943; Owen, Will, 1869-1957 (Salt Lake City, UT : Project Gutenberg, 2004)
"Breaking a Spell" by W. W. Jacobs is a humorous short story from the early 20th century. This tale falls under the category of fiction, specifically a comedic narrative that explores themes of superstition and the absurdity of witchcraft beliefs. The story focuses on a character named Joe Barlcomb, who becomes increasingly paranoid about being bewitched due to a series of unfortunate events in his life. The storyline follows Joe Barlcomb as he tries to make sense of his bad luck, which he attributes to witchcraft, leading him to consult a supposed "white witch," Mrs. Prince. After enduring a series of misfortunes including his wife$1 (Bs injury, his children's illnesses, and the death of his pig, Joe seeks Mrs. Prince's help to identify the source of his troubles. Following her peculiar advice involving buying and selling ha'pennies, Joe embarks on a comically misguided quest to discover who in his community wishes him ill. Ultimately, his foolish antics culminate in a misunderstanding that exposes the absurdity of the situation, leaving him as the subject of ridicule in his town when his actions result in unintended consequences instead of the expected resolution. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; Sailors -- Fiction